‘Cinema’ as a Modernist Conception of Motion Pictures - Betancourt, Michael (AM Časopis za studije umetnosti i medija [AM Journal of Art and Media Studies], 2018)
In the 1960s and 1970s the Clement Greenberg’s Modernist ideology of ‘purity’ played a central role in the definition of ‘avant-garde cinema’ as a serious, major genre of film. This transfer between ‘fine art’ and ‘avant-garde film’ was articulated as ‘structural film’ by P. Adams Sitney. This heritage shapes contemporary debates over ‘postcinema’ as digital technology undermines the ontology and dispositive of historical cinema. Its discussion here is not meant to reanimate old debates, but to move past them.
https://katalog.adlr.link/Record/ai-53-701363